The Effects of Tax Education and Tax Supervision During the Covid-19 Pandemic on Tax Revenue Through Tax Compliance - Said Faiz Alamien; Sugeng Mulyono; Rini Astuti; Endang Suswanti (International Journal of Economics Development Research (IJEDR), 2023)
This study sought to identify the effects of tax education and tax supervision during the Covid-19 pandemic on tax revenue through tax compliance. The population in this study was 1,550 Corporate Taxpayers engaged in the trade sector that are registered in the Singosari Tax Office. Using Slovin’s formula, 94 Taxpayers were selected as samples. Accidental sampling technique was used and data were collected by distributing questionnaires. Explanatory research using a quantitative approach was considered the most appropriate. Primary data came from respondents' answers to the questionnaire using a Likert scale of 1 to 5. Partial Least Square (PLS) was used to test the hypotheses of the study with the help of SmartPLS 4.0. The results show that tax education, tax supervision and tax compliance positively and significantly affect tax revenue, tax supervision positively and significantly affects tax compliance, tax education has no positive and significant effect on tax compliance, tax compliance cannot mediate tax education against tax revenue, and tax compliance partially mediates tax supervision against tax revenue.